Noise mapping in the EU models and procedures - Licitra, Gaetano (CRC Press, 2013)
"Protecting citizens from high noise levels and preserving quiet areas in the urban environment is a key issue for the European Community. Noise mapping is the first tool for assessing noise exposure, communicating information to citizens, and defining effective action plans. Indeed, strategic noise maps are now required for all population centres of more than 250,000 inhabitants and for major roads, railways and airports, and strategic noise maps are now becoming required for urban areas with over 100,000 people.This comprehensive reference guide for technicians and acoustics consultants shows how to integrate data with geographical information systems, improve accuracy in model and prediction software, and assess different methods and descriptors for evaluating annoyance and noise exposure. It provides guidance on regulations, communication processes for citizens involved in decision making, physical aspects, and application. Different chapters are written by European experts from a range of research institutes, companies and environmental agencies"-- Provided by publisher.
"A Spon Press book."
Keywords: Noise pollution -- European Union countries.; Noise control -- European Union countries.; elektronické knihy; electronic books